Euler-Euler simulation of wood chip combustion on a grate – effect of fuel moisture content and full scale application. (1st January 2013) - Kurz, D.; Schnell, U.; Scheffknecht, G.
Nowadays, it is common practice to perform CFD calculations for optimisation purposes of technical biomass combustion applications. A numerical model for wood chip combustion on grate firing arrangements has been developed. The model is based on an Euler-Euler approach, enabling a detailed multiphase description of the combustion chamber in terms of flow, turbulence and heat transfer. The model explicitly accounts for interactions between bed and freeboard region and comprises a global description of the whole incineration process associated with wood combustion. For validation purposes, the effect of fuel moisture content in a 240 kWth test facility has been observed experimentally and the results are opposed to the model predictions. Additionally, measurements within a 58 MWth full scale grate firing system have been conducted and the scalability of the numerical model towards industrial applications is investigated.